PENERAPAN GOAL PROGRAMMING PADA PERENCANAAN OPTIMISASI ASET, LIABILITAS, EKUITAS, PENDAPATAN DAN BEBAN (STUDI KASUS: BANK 9 JAMBI) - GINTING, YEMIMA PIPIYANTI Br; ROZI, SYAMSYIDA; RARASATI, NIKEN (E-Jurnal Matematika, 2024)
Bank 9 Jambi requires optimization planning to maintain financial balance. The optimization is relate to five objectives that are maximize assets, minimize liabilities, maximize equity, maximize income, and minimize expenses. Therefore, the aim of this research was to analyze the possibility of optimization in financial report in Bank 9 Jambi. Because there are 5 objectives which were considered in this research, so the model applied is goal programming. By the result of goal programming, it was confirmed that Bank 9 Jambi can meet five goals as desired. Besides, in this research, sensitivity analysis was performed to identify whether the result of goal programming will be changed or not, especially the sensitivity analysis of right side of inequality in the constraints of the model. And the result of sensitivity analysis is that the five goals will still be met as long as the limit of total asset for 1.5 years is in the interval of IDR 75,314,347 million to IDR 77,831,122 million, the limit of minimum total liability is IDR 66,719,681 million, the limit of equity target is in the interval IDR 11,111,441 million to Rp.11. 482,751 million, the limit of total income is in the interval IDR 0 to IDR 6,542,843 million and the limit of total expense is at least IDR 1,435,052 million.